To move or not to move? A study of sustainable retirement village in Malaysia - Lim, Xin-Jean; Ng, Siew Imm; Kamal Basha, Norazlyn; Cheah, Jun-Hwa; Ting, Hiram (Springer New York LLC, 2020)
Sustainability is now on the forefront on a wide variety of global debates, which is hardly surprising given its emphasis to enhance the well-being of society in an increasingly challenging world. The rapid aging of developing societies has compelled policymakers and developers to provide adequate housing options that meet the diverse needs of elderly populations. As a result, sustainable retirement village (SRV) has emerged as a novel relocation option in meeting the needs of the elderly by providing them an affordable and comfortable living space. Thus, the present study aims to elucidate the multifaced aspects of sustainability features (i.e., social, environmental, and economic aspects) that affect the elderly’s willingness to move into retirement village. A self-administrative survey was adopted to collect data from 261 elderly in Malaysia aged 50 years old and above. The analysis of the structural model has shown that sustainability in the aspect of social and environmental, positively impact on the attitude towards SRV. Besides that, communicability was also found to moderate the path between economic sustainability and attitude as well as attitude towards willingness to move into SRV. The paper concludes with limitations and recommendations for future research.